Nutritional Value, Therapeutic Effects, Phytochemistry, and Toxicology of Lepisanthes fruticosa: A Review - Siang, Lim J.; Rajak, Harish; Ravichandran, Veerasamy (Current Topics in Medicinal Chemistry, 2024)
The multifaceted benefits of Lepisanthes fruticosa position it is not only as a promising agricultural commodity but also as a versatile resource with implications for health, biodiversity, and economic growth. Lepisanthes fruticosa has a rich history of traditional use for treating various ailments such as fever and diarrhea. Beyond its traditional uses, the plant's antioxidant properties suggest potential applications in combating oxidative stress-related conditions. Its antihyperglycemic properties indicate promise in managing elevated blood sugar levels, while its antibacterial and antiviral attributes hint at potential applications in infectious disease control. Furthermore, the plant's anticancer properties add to its appeal as a valuable resource in the realm of medical research. The plant also exhibits considerable potential in addressing a range of health concerns, including non-communicable diseases and infections, antidiarrheal, and antiviral properties. In essence, Lepisanthes fruticose emerges as more than just an agricultural asset. Its unique combination of nutritional richness, health benefits, and economic viability underscores its potential to become a valuable asset both locally and on the global stage. In this current review, we are discussed about the ethnopharmacology, nutritional value, therapeutic effects, phytochemistry, and toxicology of Lepisanthes fruticose.
Keywords: Nutritional value